Cognitive and affective functions in Alzheimer's disease patients with metabolic syndrome. (23rd October 2015) - Hishikawa, N.; Fukui, Y.; Sato, K.; Kono, S.; Yamashita, T.; Ohta, Y.; Deguchi, K.; Abe, K.
Abstract : Background and purpose: The influence of metabolic syndrome (MetS) on cognitive and affective functions in patients with Alzheimer's disease (AD) was examined. Methods: A total of 570 AD patients were divided into two subgroups depending on waist circumference (WC) (normal versus achieving Japanese diagnostic criteria of MetS). Afterwards, the AD control subgroup was defined as those normal WC patients with no vascular risk factors (VRFs). The AD with MetS (AD‐MetS) subgroup was defined as the MetS WC group who had two or more VRFs to qualify as having MetS. Cognitive and affective functions, insulin resistance, vascular endothelial function and white matter changes between AD‐MetS and AD controls were compared. Results: Scores on the Mini‐Mental State Examination, Hasegawa Dementia Score – Revised, Frontal Assessment Battery and Montreal Cognitive Assessment were worse in the AD‐MetS group than in AD controls, but the difference was not significant. Some analyses were conducted twice, once including all patients and once including only late‐elderly patients. Scores on the Geriatric Depression Scale were found to be significantly higher for AD‐MetS than for AD controls (all ages, late‐elderly), as were those for apathy (late‐elderly). Furthermore, both the homeostasis model assessment of insulin resistance and reactive hyperemia index scores were significantly worse in AD‐MetS than in AD controls, whilst white matter changes showed a tendency to be worse. Conclusions: Greater cognitive and affective decline occurs in patients with AD‐MetS than in those without. Further, insulin resistance and vascular endothelial dysfunction are strongly correlated with AD‐MetS before pathological white matter changes can be observed. Abstract : Clickhere to view the accompanying paper in this issue.